Origin of Bahariya oil in Salam oil field, Western Desert- Egypt - E.A. Abd El-Gawad; D.A. Mousa; M.A. Lotfy; A.I. El-Shorbagy (Egyptian Journal of Petroleum)
The origin of Bahariya oil is a debatable issue. Bahariya Formation produces oil from the Lower sandstone unit by normal pressure mechanism, while the Upper Bahariya shale produces oil by fracking mechanism. The main question is: is there any genetic relationship between the two oils.To answer this question, “50” ditch samples, “12” extract samples and “2” oil samples represent Khatatba and Bahariya formations and Abu Roash ‘G’ Member, collected from six wells drilled in Salam oil field, have been geochemicaly analyzed, using LECO SC632, Rock–Eval- 6 pyrolysis, GC and GC/MS techniques.The analysis shows that the Total Organic Carbon content (TOC) for the studied formations ranges from fair to v.good, with poor to good hydrocarbon potentiality. The maturity evaluation using Tmax, and calculated Vitrinite reflectance (Ro) showed that the studied samples have good thermal maturation reaching the stage of oil generation. Also the analysis revealed that the kerogen is a mixture of type II/III kerogen, reflecting the potential generation of oil and gas. The GC and GC/MS data showed that the organic matter is a mixed marine/terrestrial input deposited in transitional environment under prevailing reducing conditions. The oil samples fingerprint of the saturated hydrocarbons fraction from Baharyia reservoir (Lower and Upper) members suggest that the oil samples have a mixed organic source with significant terrestrial organic matter input deposited under saline to hypersaline environment with slightly oxidizing environment.Based on the obtained results, it is suggested that the Bahariya oil has been sourced mainly from deeper horizons (Khatatba Formation) with some contribution from upper and lower Bahariya source rocks. Keywords: Rock Eval -6, Kerogen type, Geochemical analysis, GC and GC/MS analysis